IMPLEMENTASI APLIKASI ARSIP DOKUMEN UNTUK MENDUKUNG PROSES BISNIS PADA PT. XXX: Implementation of Document Archive Application to Support Business Processes at PT. XXX - Tjiptabudi, Fransiskus Mario Hartono; Ndaumanu, Ricky Imanuel (Jurnal Sains Komputer dan Teknologi Informasi, 2024)
Document archiving is a very important supporting factor for a company's business processes. In accordance with KUHD, which states that the document retention period in a company is 10 years, then of course company’s must apply the right document archiving method to ensure the condition, availability and ease of document retrieval. The status of document archiving at PT XXX so far still uses the form of hardcopy, which certainly begins to take up document storage space. In addition, searching for documents takes time and effort, even though the archives are well organized and classified. Another obstacle is that electronic mail and mail attachments sent via electronic mail are also difficult to archive with a clear classification. By taking advantage of technological developments, various types of documents such as letters, reports, and other types of documents can be archived not only in the hardcopy form, but also in the form of digital copies (softcopy). Therefore, PT. XXX needs a computer application that can help archive documents digitally, both for documents in the hardcopy form and documents from electronic mail. The goal is that PT. XXX can implement good document governance so that it can support the business processes carried out. Through this research, the application will be built by applying the GXP development model, which will produce various document management features, namely scanning, synchronization with electronic mail, classification, storage, and search and digital document preview. Through the results of user testing, it is found that the application through its various features can help PT. XXX to manage document archives and support its business processes.